Optimizing Public Relations Management to Strengthen the Role of Alumni and Community Leaders - Samsul Arifin; M. Kurma Nur Faifatur R; Sumarsi Sumarsi; Hartinah Hartinah; Khatipah Khatipah (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
Public relations management strategies in building and strengthening synergistic relationships between MTs Nurul Wafa Besuki Situbondo and alumni and community leaders. This is a qualitative study using a case study approach. Data was obtained through direct observation, in-depth interviews with the head of the madrasah, public relations officers, alumni, and community leaders, and supported by documentation of public relations activities. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing in accordance with the Miles and Huberman model. The results of the study show that the public relations strategy at MTs Nurul Wafa emphasizes two-way communication based on Islamic values, such as ukhuwah islamiyah (Islamic brotherhood), openness, and honesty. Through social events, digital publications, and socio-religious activities, public relations has succeeded in increasing public trust and strengthening the madrasah's positive image. Alumni act as communication agents and sources of moral and material support, while community leaders become strategic partners in expanding the institution's influence and legitimacy. The integration of Islamic boarding school values with communication professionalism makes MTs Nurul Wafa's public relations strategy effective in building the institution's reputation as an Islamic institution that is adaptive to the times.